Exploring Changes in Ocular Aberrations for Different Fixation and Accommodation Stimuli - María Mechó-García; Rute J. Macedo-de-Araújo; Paulo Fernandes; José Manuel González-Méijome (Photonics)
Background: Given the lack of standardization in stimulus types for assessing accommodation, we aimed to evaluate accommodative response (AR) and Zernike coefficients using four different stimuli. Methods: Sixteen healthy subjects aged 22–32 years participated. Four black transilluminated stimuli (Snellen 6/12 “E”, 6/6 “e”, Maltese Cross 6/12 “X”, 6/6 “x”) were used to stimulate accommodation from 0 D to 5 D, in 1 D increments, using the irx3 aberrometer. From the results, AR was calculated with Seidel defocus and the change in Zernike coefficient value between the non-accommodative state and the fully accommodative state (5 D) was determined. Results: Larger pupils were observed with stimulus “E” (p-value < 0.05). The mean AR at the maximum accommodative level (5 D) for the different stimuli was −1.88 ± 1.00 for “E”, −2.60 ± 1.44 for “X”, −2.00 ± 1.32 for “e”, and −2.40 ± 1.27 for “x”. No statistically significant differences were found between AR and Zernike coefficients with the four different accommodative stimuli (p-value > 0.05, one-way ANOVA). Conclusions: The study evaluated accommodative stimulus design and size on AR and Zernike coefficients and found no significant differences. However, stimuli with higher spatial frequencies (“e” and “E”) provided larger ARs compared to the other stimuli.